Implementasi Shopping Cart Berbasis Android Untuk Aplikasi Pemesanan Di CV Karya Belia Nusantara - Hambali, Dede; Febrian, Rio; Mangaratua Simatupang, Yosua (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Advances in mobile technology have encouraged small and medium enterprises (SMEs) to adopt digital systems to improve service efficiency. CV Karya Belia Nusantara, a local product distribution company, requires a modern ordering system that is flexible and accessible to customers. This research aims to implement an Android-based shopping cart feature that supports a fast, practical, and structured product ordering process. The development method used is Agile Development, while the main technologies implemented include Kotlin for Android development and Firebase Realtime Database for data storage.